HUBUNGAN ASUPAN MAKANAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS BABUSSALAM KABUPATEN ACEH TENGGARA - Taufik Hidayat; Rohani (Jurnal Kesehatan Tambusai, 2022)
Nutritional status in childhood is a very important determinant of health in the future. One of the nutritional problems that gets a lot of attention in toddlers is stunting. Stunting is stated as a stunting syndrome that can cause several pathological changes, characterized by linear growth retardation, increased morbidity and reduced physical and neurodevelopmental abilities/capacities. This study aims to determine the relationship between food intake (energy intake and protein intake) with the incidence of stunting in children under five in the working area of ​​Babussalam Public Health Center, Southeast Aceh Regency. The research method is quantitative with a cross-sectional study design. The collection of samples using purposive sampling method obtained 38 samples and instruments used in the form of measuring body weight and height (microtoice) and food frequency questionnaires semiquantitative. Based on the results of statistical tests, it was found that there was a relationship between food intake (energy intake) and the incidence of stunting in children under five with p-value = 0.004 and there was a relationship between food intake (protein intake) and stunting in children under five with p-value = 0.012. So it is suggested to the community in the working area of ​​the Babussalam Public Health Center, Southeast Aceh Regency, the need to prevent stunting as early as possible, especially to families, namely mothers so that they can provide adequate nutritional intake so that they can reduce the risk of stunting in toddlers and pregnant women can maintain their diet according to balanced nutrition so that not giving birth to low birth weight babies so as to reduce the risk of stunting in toddlers.